Sosialisasi Dan Pendampingan Pembuatan Nomor Induk Berusaha (NIB) Melalui Online Single Submission (OSS) Untuk Mitra UMKM Tape Desa Musir Kidul Dusun Semen - Maulana, Hendra; Handayani, Alfia Indah; Fitrianata, Muhammad Ikhsan; Fakhiroh, Luqy Aizzatul; Sijabat, Riris Oktauli BR; Nakrowiyah, Finda Rohmatin (Universitas Gajah Putih, Indonesia, 2023)
As a rule of law and in accordance with Indonesian government regulations, a business license is an important component for running a business or business, because it relates to business permits for legal entities and individuals. Even so, not a few MSME business actors in Indonesia still do not have legality for their business. Through community service activities, the UPN Veteran UPN Veterans Thematic MBKM Real Work Lecture Group 67 tried to help provide socialization and assistance for making Business Identification Numbers (NIB) for MSMEs in Musir Kidul village, Nganjuk. The service team succeeded in socializing and assisting MSME Tape Pak Lan village of Musir Kidul for making Business Identification Numbers, where activities were carried out through the main stages of observation, socialization (counseling), and assistance in making NIB through the OSS system.